CGIAR Research Program on Grain Legumes and Dryland Cereals - Plan of Work and Budget 2020 - CGIAR Research Program on Grain Legumes and Dryland Cereals (CGIAR Research Program on Grain Legumes and Dryland Cereals, 2020)
The Theory of Change for FP1 remains largely unchanged and the team is making efforts to ensure that adequate progress is made towards the set outcome targets. For FP3, no adjustment was made to date, but some changes may occur following the flagship meeting in the first quarter of 2020 when the ToC will be revisited. Similarly, there are currently no major changes in the Theories of Change (ToC) for FP4 and FP5.